2022
DOI: 10.3390/microorganisms10081484
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Graminearum Virus-1 Strain FgV1-SD4 Infection Eliminates Mycotoxin Deoxynivalenol Synthesis by Fusarium graminearum in FHB

Abstract: Deoxynivalenol (DON) toxin production during the infection of F. graminearum in small grain crops is one of the most harmful virulence factors associated with economic losses. Metatranscriptome sequencing and RT-qPCR traced back that the only mycovirus infecting an F. graminearum isolate, designated as Fg-4-2, was a novel strain of Fusarium graminearum virus 1 (FgV1), designated as FgV1-SD4. The isolate Fg-4-2 showed significantly reduced virulence against wheat compared to the virus-free culture, designated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Lack of symptoms has also been observed for Sclerotinia sclerotiorum fusarivirus 1 [ 8 ]. Fusarium graminearum virus 1 strain SD4 causes hypovirulence and eliminates deoxynivalenol synthesis in Fusarium graminearum [ 9 ].…”
Section: Pathogenicitymentioning
confidence: 99%
“…Lack of symptoms has also been observed for Sclerotinia sclerotiorum fusarivirus 1 [ 8 ]. Fusarium graminearum virus 1 strain SD4 causes hypovirulence and eliminates deoxynivalenol synthesis in Fusarium graminearum [ 9 ].…”
Section: Pathogenicitymentioning
confidence: 99%
“…dianthi mycovirus 1, and Fusarium pseudograminearum megabirnavirus 1 (FpgMBV1), cause hypovirulence 225 . Moreover, FgV1 and FgHV2 infections can reduce DON production in F. graminearum 226 , 227 . Li et al 228 found that FpgMBV1 eliminates DON accumulation by downregulating the expression of TRI biosynthetic genes.…”
Section: The Management Strategy For Fusarium Myco...mentioning
confidence: 99%
“…Some species not only reduce yield production and value of cereals but produces toxins in crops which can disturb the health of animal and human. Now, mycoviruses have been reported in Fusarium graminearum, F. solani, F. oxysporum, F. poae, F. virguliforme and F. boothii [80,83,[87][88][89][90]. Fusarium viruses belong to Totiviridae, Partitiviridae and Chrysoviridae [91].…”
Section: Mycoviruses Of Fusariummentioning
confidence: 99%